An accurate tool for ageing Two‐spined Blackfish for use in determining timing of spawning in upland streams in the Brindabella ranges, ACT, Australia. (5th January 2016) - Dennis, Lachlan P.; Broadhurst, Ben T.; Lintermans, Mark
Summary: To manage populations of threatened fish species in modified habitats and regulated rivers requires an understanding of their reproductive biology and spawning cues. In particular, accurate information about early life stages in these species can be used to facilitate programmes that maximise recruitment and breeding success. This study aimed to develop methods to accurately age early juvenile freshwater native fish, Two‐spined Blackfish, (Gadopsis bispinosus), to allow the determination of spawning date. This was accomplished through the examination of otolith microstructure in early juveniles. The age at which the first ring was deposited and the relationship between days and number of rings were determined using both field and aquarium trials. Field trials of marked juvenile otoliths revealed daily deposition of rings (1.02 ± 0.02 rings per day for fish sacrificed six days postmarking). The strength of this relationship lessened slightly as juveniles aged (0.92 ± 0.02 rings per day for fish sacrificed 13 days postmarking). The first otolith ring was deposited 7.50 ± 1.09 days after spawning. The enumeration of daily rings combined with knowledge of the commencement of ring deposition enabled accurate estimation of spawning date. The current study is the first to examine otolith microstructure in juvenile Two‐spined Blackfish allowing accurate determination of spawning date. While more research is required to accurately age older juveniles, this technique has the potential to precisely correlate spawning with environmental cues, facilitating better management of temperature and flow during breeding periods, potentially increasing spawning and recruitment of this endangered species.